2015
DOI: 10.1002/btpr.2156
|View full text |Cite
|
Sign up to set email alerts
|

From water‐in‐oil to oil‐in‐water emulsions to optimize the production of fatty acids using ionic liquids in micellar systems

Abstract: Biocatalysis is nowadays considered as one of the most important tools in green chemistry. The elimination of multiple steps involved in some of the most complex chemical synthesis, reducing the amounts of wastes and hazards, thus increasing the reaction yields and decreasing the intrinsic costs, are the major advantages of biocatalysis. This work aims at improving the enzymatic hydrolysis of olive oil to produce valuable fatty acids through emulsion systems formed by long alkyl chain ionic liquids (ILs). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 60 publications
(108 reference statements)
0
14
0
Order By: Relevance
“…Santos et al [15] studied the effect of an emulsion system formed by long alkyl chain ionic liquids on the enzymatic hydrolysis of olive oil. They demonstrated that although at low water concentrations (water-in-oil emulsion) the presence of emulsion does not present any advantage for the hydrolysis reaction, at high water content (oil-in-water emulsion), the ionic liquid acts as an enhancer of lipase catalytic activity, super-activating 1.8 times the enzyme.…”
Section: Sustainable Procedures For Soapstock Hydrolysis By Enzymaticmentioning
confidence: 99%
“…Santos et al [15] studied the effect of an emulsion system formed by long alkyl chain ionic liquids on the enzymatic hydrolysis of olive oil. They demonstrated that although at low water concentrations (water-in-oil emulsion) the presence of emulsion does not present any advantage for the hydrolysis reaction, at high water content (oil-in-water emulsion), the ionic liquid acts as an enhancer of lipase catalytic activity, super-activating 1.8 times the enzyme.…”
Section: Sustainable Procedures For Soapstock Hydrolysis By Enzymaticmentioning
confidence: 99%
“…From the literature study, it is realized that lipases derived from C. rugosa are found to be most prominent biocatalysts in catalyzing various types of reactions including hydrolysis of conjugated linoleic acid l‐methyl ester by addition of an organic solvent, transesterification of palm oil with methanol and ethanol, enantioselective hydrolysis of menthol benzoate, etc. Another important yeast source of lipase is C. antactica , which is effectively used for the synthesis of valuable fatty acids, production of biodiesel through transesterification of Simarouba glauca oil, production of pharmaceutical products through acylation and alcoholysis, synthesis of cosmetic and detergent products by acidolysis of butter oil with conjugated linoleic acid and acidolysis of acyl glycerols . Further, yeast lipases are effectively used in biodiesel production that includes lipases from T. lanuginosus used in hydroesterification of soybean oil; Rhodotorula mucilaginosa used in esterification of palm oil; T. lanuginosus used in hydrolysis of soybean oil and T. lanuginosus used in transesterification of rapeseed oil .…”
Section: Sources Of Lipasesmentioning
confidence: 99%
“…Further the details about yeast and bacterial lipases and their application in hydrolysis reactions are given in Tables and . It has been reported that the enzymatic hydrolysis of olive oil to produce valuable fatty acids can be improved through emulsion systems formed by long alkyl chain ionic liquids (ILs) …”
Section: Lipase‐catalyzed Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although this conventional method produces high conversion yield, it requires high temperature (100–260 °C) and pressure (100–7000 kPa), thus causing undesirable reactions such as dehydration, oxidation of fatty acids, and interesterification of triglyceride . Oil hydrolysis using lipase as a biocatalyst has received considerable attention for the production of fatty acids . This method is more advantageous than the conventional method because the method can be employed at low temperatures and demonstrates high selectivity, thus leading to energy conservation and obtaining high‐purity products .…”
Section: Introductionmentioning
confidence: 99%